Iron and a mixture of DHA and EPA supplementation, alone and in combination, affect bioactive lipid signalling and morbidity of iron deficient South African school children in a two-by-two randomised controlled trial. (February 2016) - Malan, L.; Baumgartner, J.; Zandberg, L.; Calder, P.C.; Smuts, C.M.
Abstract: We recently reported that iron supplementation increased respiratory morbidity in iron deficient South African children. This increase, however, was attenuated when iron was provided in combination with a mixture of DHA/EPA. To explore potential underlying mechanisms, we examined the effects of iron and DHA/EPA, alone and in combination, on plasma lipid-derived immune modulator concentrations and related gene expression in peripheral blood mononuclear cells (PBMC). DHA/EPA decreased inflammatory 12-hydroxyeicosatetraenoic acid and tended to increase anti-inflammatory and pro-resolving 17-hydroxydocosahexaenoic acid (17-HDHA), while iron decreased 17-HDHA. However, in combination with iron, the anti-inflammatory effect of DHA/EPA was maintained. These biochemical changes may explain the prevention of iron-induced respiratory morbidity that we observed when iron was supplemented in combination with DHA/EPA during the 8.5 month randomised controlled trial and might lead to a safer approach of delivering iron supplementation. The study was registered at clinicaltrials.gov as NCT01092377.